InterCom (1974) - Office of Public Relations. Duke University Medical Center (1974)
Volume 21, numbers 1-47; January 4, 1974; January 11, 1974; January 19, 1974; January 25, 1974; February 1, 1974; February 8, 1974; February 15, 1974; February 22, 1974; March 1, 1974; March 8, 1974; March 15, 1974; March 22, 1974; March 29, 1974; April 5, 1974; April 12, 1974; April 19, 1974; April 26, 1974; May 3, 1974; May 10, 1974; May 17, 1974; May 24, 1974; May 31, 1974; June 7, 1974; June 14, 1974; June 21, 1974; June 28, 1974; July 12, 1974; July 19, 1974; August 2, 1974; August 9, 1974; August 16, 1974; August 23, 1974; August 30, 1974; September 6, 1974; September 13, 1974; September 20, 1974; September 27, 1974; October 4, 1974; October 11, 1974; October 18, 1974; October 25, 1974; November 1, 1974; November 8, 1974; November 15, 1974; November 22, 1974; December 6, 1974; December 13, 1974; December 20, 1974. June 14, 1974 issue mislabeld Volume 24, Number 21; corrected in pencil to Volume 21, Number 23.5. Break for week of Independence Day; no issue Christmas week. Published weekly for Duke University Medical Center employees, faculty, staff, students, and friends by the Medical Center Public Relations Office, Joe Sigler, Director. David Williamson, Editor. Mrs. Dale Moses, Co-Editor (-September 20, 1974). Margaret Howell, Associate Editor (September 20, 1974-).